Experimental investigations of wooden beam ends in masonry with interior insulation: Measured data in real-scale experimental walls exposed to semi-continental climatic conditions. (November 2019) - Kopecký, Pavel; Staněk, Kamil; Bureš, Michal; Richter, Jan; Ryparová, Pavla; Tywoniak, Jan
This article deals with the hygrothermal performance of wooden beam ends embedded in brick masonry walls. The real-scale experiment involving three interior insulation systems with different water vapor resistances and different treatments of joist pockets was monitored for three consecutive years. The moisture load of test walls was controlled during the experiment. First, humidity of indoor air was increased in the cold season (2016–2017). Then, an artificial short-time intensive rain event brought liquid water onto the external surface of the test walls in July 2017. Despite relatively mild external climatic loads, relative humidity was unsatisfactorily high in unsealed joist pockets. Vapor and airtight sealing of the joist pockets improved the microclimate of the wooden beam ends. However, even in this case, relative humidity approached critical values for the onset of mold growth. The artificial rain load applied on the experimental walls noticeably worsened the hygrothermal conditions in the joist pockets. Relative humidity in the joist pockets further increased to a level where massive mold growth could be expected. Visual inspection of the wooden beam ends during reconstruction of the experiment, however, revealed only a small spot of mold on a single beam located in an unsealed joist pocket. Mold growth on samples of organic thermal insulation material was found by microscopic investigations. Molds were localized in small separated colonies. These in situ and laboratory investigations do not confirm the calculated values of mold growth index. In conclusion, sealing of wooden beam ends improved their hygrothermal performance in the experiment.